Pharmacological Classes of Conus Peptides Targeted to Calcium, Sodium, and Potassium Channels - Isdiany, Nitta; Rahmat, Mamat; Pramintarto Eko Mulyo, Gurid; Judiono; Jimenez, Elsie C. (Protein and Peptide Letters, 2023)
This review describes the specific features of families of Conus venom peptides (conotoxins or conopeptides) that represent twelve pharmacological classes. Members of these conopeptide families are targeted to voltage-gated ion channels, such as calcium, sodium, and potassium channels. The conopeptides covered in this work include omega-conotoxins and contryphans with calcium channels as targets; mu-conotoxins, muO-conotoxins, muP-conotoxins, delta-conotoxins and iota-conotoxin with sodium channels as targets; and kappa-conotoxins, kappaM-conotoxins, kappaO-conotoxin, conkunitzins, and conorfamide with potassium channels as targets. The review covers the peptides that have been characterized over the last two decades with respect to their physiological targets and/or potential pharmacological applications, or those that have been discovered earlier but with noteworthy features elucidated in more recent studies. Some of these peptides have the potential to be developed as therapies for nerve, muscle, and heart conditions associated with dysfunctions in voltage-gated ion channels. The gating process of an ion channel subtype in neurons triggers various biological activities, including regulation of gene expression, contraction, neurotransmitter secretion, and transmission of electrical impulses. Studies on conopeptides and their interactions with calcium, sodium, and potassium channels provide evidence for Conus peptides as neuroscience research probes and therapeutic leads.
Keywords: Conus peptide pharmacological classes